2015
DOI: 10.1093/mnras/stv2284
|View full text |Cite
|
Sign up to set email alerts
|

Milimetre-band variability of the radio-quiet nucleus of NGC 7469

Abstract: We report short-cadence monitoring of a radio-quiet (RQ) Active Galactic Nuclei (AGN), NGC 7469, at 95 GHz (3 mm) over a period of 70 days with the CARMA telescope. The AGN varies significantly (±3σ from the mean) by a factor of two within 4-5 days. The intrinsic 95 GHz variability amplitude in excess of the measurement noise (10%) and relative to the mean flux is comparable to that in the X-rays, and much higher than at 8.4 GHz. The mm-band variability and its similarity to the Xray variability adds to the ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 46 publications
8
49
0
Order By: Relevance
“…In terms of luminosity, Laor & Behar (2008) used the PG quasar sample (Schmidt & Green 1983) to demonstrate that LR and LX are correlated and follow the well established LR/LX ∼ 10 −5 correlation observed in coronally active cool stars (Güdel & Benz 1993). In terms of variability, the sole mm-wave monitoring campaign of Baldi et al (2015) indicate the variability parameters of NGC 7469 at 95 GHz are similar to those of NGC 7469 in (non-simultaneous) archival X-ray data, only with much larger uncertainties. However, in order to truly test the connection between the mm-wave and X-ray sources of RQ AGN, simultaneous monitoring is essential.…”
Section: Connection To X-raysmentioning
confidence: 92%
See 1 more Smart Citation
“…In terms of luminosity, Laor & Behar (2008) used the PG quasar sample (Schmidt & Green 1983) to demonstrate that LR and LX are correlated and follow the well established LR/LX ∼ 10 −5 correlation observed in coronally active cool stars (Güdel & Benz 1993). In terms of variability, the sole mm-wave monitoring campaign of Baldi et al (2015) indicate the variability parameters of NGC 7469 at 95 GHz are similar to those of NGC 7469 in (non-simultaneous) archival X-ray data, only with much larger uncertainties. However, in order to truly test the connection between the mm-wave and X-ray sources of RQ AGN, simultaneous monitoring is essential.…”
Section: Connection To X-raysmentioning
confidence: 92%
“…In this paper, we report results from a dedicated monitoring campaign of NGC 7469 with the single 30 m dish of the Institut de Radioastronomie Millimetrique (IRAM) at 95 GHz and at 143 GHz, simultaneous with Swift/XRT and Swift/UVOT monitoring that was part of a multiwavelength campaign during the last part of 2015 (Behar et al 2017 was observed with CARMA Baldi et al 2015), and at 350 GHz with ALMA (Izumi et al 2015).…”
Section: Connection To X-raysmentioning
confidence: 99%
“…In this work we make use of simulated halo catalogues extracted from a set of high resolution N-body simulations (Baldi 2012) of the standard ΛCDM cosmology, performed with the C-GADGET module (Baldi et al 2010). We adopt a model consistent with WMAP7 constraints (Komatsu et al 2011), with σ 8 = 0.809, h 0 = 0.703, Ω λ = 0.7289, Ω M = 0.2711, Ω b = 0.0451, and a power spectrum with an initial scalar amplitude of A s = 2.194 · 10 −9 and a primordial spectral index of n s = 0.96.…”
Section: Simulated Halo Cataloguesmentioning
confidence: 99%
“…The Baldi et al 2015 andPronik 1976). On the basis of the dramatic spectral-variability of the optical Notes.…”
Section: Broad Componentmentioning
confidence: 99%